Fluoride sorption from aqueous solution using Al(OH)3-modified hydroxyapatite nanosheet. (1st November 2020) - Huang, Shaomeng; Hu, Minglei; Li, Dan; Wang, Liping; Zhang, Can; Li, Kang; He, Qiongqiong
Highlights: Hydroxyapatite with lattice defect (4% calcium deficiency) was prepared with EDTA. Al(OH)3-hydroxyapatite with high Al/Ca molar ratio was prepared. High defluoridation capacity, 194.2 mg/g in neutral condition at 318 K. The concentrations of Al 3+, Ca 2+ and F − in dissolution experiment were low. Abstract: In this study, Al(OH)3 -hydroxyapatite nanosheet (Al(OH)3 -nHAP), an adsorbent of high defluoridation capacity, was prepared based on the nano hydroxyapatite (nHAP) with lattice defect (4% calcium deficiency) brought by the addition of EDTA. And the composite was characterized by XRD, TEM-EDS, FT-IR and N2 adsorption method. The effects of adsorbent dosage, pH value, initial fluoride concentration and co-existing ions to the adsorption behaviors were studied, and then kinetics, isotherms, thermodynamics, ion exchange rate, regeneration and dissolution were investigated. The maximum defluoridation capacity of Al(OH)3 -nHAP nanosheet were 141.84, 171.88 and 194.2 mg/g at 298, 308 and 318 K in neutral condition with the initial fluoride concentration of 200 mg/L. The high defluoridation capacity was due to the high Al/Ca atomic ratio (1.44). The nHAP with lattice defect might help Al atoms to dope into the nHAP. About 22.14% of Al atoms was doped into the lattice of nHAP and 77.86% was loaded on the surface of nHAP by modifying. Ca9.6 (PO4 )6 (OH)1.2 and 8.5156Al(OH)3 -Ca7.5792 Al2.4208 (PO4 )6 (OH)4.4208 was proposed as the chemical formula of nHAP and Al(OH)3 -nHAP synthesized in this study via calculations. The adsorption performance followed the Pseudo-second-order kinetic model and Freundlich isotherm model, which was a spontaneous and endothermic process. The removal efficiency of regenerated Al(OH)3 -nHAP nanosheet always stayed above 81.32% and showed good stability during the four cycles. The concentrations of Al 3+, Ca 2+ and F − in dissolution experiment were 0.01, 2.11 and 0.56 mg/L, respectively, indicating its safety and stability.